Determination of trichloroacetic acid in environmental studies using carbon 14 and chlorine 36 - Matucha, Miroslav; Rohlenová, Jana; Forczek, Sándor T; Uhlírová, Hana; Gryndler, Milan; Fuksová, Kvetoslava; Schröder, Peter (Chemosphere, 2006)
Radioisotopes carbon 14 and chlorine 36 were used to elucidate the environmental role of trichloroacetic acid (TCA) formerly taken to be a herbicide and a secondary air pollutant with phytotoxic effects. However, use of 14C-labeling posed again known analytical problems, especially in TCA extraction from the sample matrix. Therefore--after evaluation of available methods--a new procedure using decarboxylation of [1,2-14C]TCA combined with extraction of the resultant 14C-chloroform with a non-polar solvent and its subsequent radiometric measurement was developed. The method solves previous difficulties and permits an easy determination of amounts between 0.4 and 20 kBq (10 - 500 ng g(-1)) of carrier-less [1,2-14C]TCA in samples from environmental investigations. The procedure is, however, not suitable for direct [36Cl]TCA determination in chlorination studies with 36Cl. Because TCA might be microbially degraded in soil during extraction and sample storage and its extraction from soil or needles is never complete, the decarboxylation method--i.e. 2 h TCA decomposition to chloroform and CO2 in aqueous solution or suspension in closed vial at 90 degrees C and pH 4.6 with subsequent CHCl3 extraction-is recommended here, estimated V < 7%. Moreover, the influence of pH and temperature on the decarboxylation of TCA in aqueous solution was studied in a broad range and its environmental relevance is shown in the case of TCA decarboxylation in spruce needles which takes place also at ambient temperatures and might amount more than 10-20% after a growing season. A study of TCA distribution in spruce needles after below-ground uptake shows the highest uptake rate into current needles which have, however, a lower TCA content than older needle-year classes, TCA biodegradation in forest soil leads predominatingly to CO2.
Keywords: Ecosystem; Trichloroacetic Acid; Decarboxylation; monitorování životního prostředí; ekosystém; nadzemní části rostlin; látky znečišťující půdu; koncentrace vodíkových iontů; Trees; Chlorine; Carbon Radioisotopes; dekarboxylace; chloroform; teplota; stromy; půda; Environmental Monitoring; Soil Pollutants; Plant Components, Aerial; Soil; chlor; Hydrogen-Ion Concentration; Chloroform; kyselina trichloroctová; radioizotopy uhlíku; Temperature